LEADERSHIP STYLE OF SALES MANAGER: A CRITICAL ANALYSIS ON IMPACT ON SALES PERFORMANCE - Agrawal, Akash Deepak (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Any organization's sales department is an essential vertical as it has a direct impact on both top-line revenue and bottom-line profitability. In order to inspire sales executives to support and accomplish company objectives, effective sales leadership is essential. As a result, it is crucial to cultivate a solid and constructive connection between sales managers and sales executives. The purpose of this study is to investigate how the leadership styles of sales managers affect the output of sales teams. Two prominent businesses in the BFSI sector, which has seen tremendous expansion in recent years, are the subject of the study. Interestingly, the ICICI group has become a major force in this industry. Maintaining and improving performance results requires that sales managers and sales teams be properly aligned.